Pickering emulsions stabilised by hydrophobically modified cellulose nanocrystals: Responsiveness to pH and ionic strength. (February 2020) - Du Le, Hoang; Loveday, Simon M.; Singh, Harjinder; Sarkar, Anwesha
Abstract: The aims of this study were to hydrophobically modify cellulose nanocrystals (CNCs), investigate the ability of such modified CNCs (MCNCs) to stabilise Pickering oil-in-water (O/W) emulsions and understand their stability at different pHs (2.0–7.0) and ionic strengths (0–150 mM NaCl). Structural changes that resulted from esterifying CNCs with octenyl succinic anhydride (OSA) were determined using Fourier transform infrared (FTIR) spectroscopy, X-ray diffractometry (XRD), transmission electron microscopy (TEM) and wettability analysis. The stability of the Pickering O/W emulsions (20 wt% oil, 0.05–1.00 wt% MCNCs) was assessed using droplet sizing, microscopy, ζ-potential, apparent viscosity and oscillatory rheological measurements. FTIR spectroscopy confirmed a decrease in the intensity of the –OH-associated band because of reaction of the hydroxyl groups with OSA. XRD indicated a lower (11.5%) crystallinity index in MCNCs. TEM revealed that there was no change in morphology of the needle-shaped CNCs upon OSA modification (length/diameter = 40–100 nm/2–4 nm). Hydrophobic modification of CNCs with OSA was evidenced by an increase in static water contact angle from 56° (untreated CNCs) to 80.2° (MCNCs) which allowed the MCNCs to be partially wetted by both the phases and stabilise O/W emulsions. The Pickering emulsions showed droplet flocculation at pH < 4.0 (without addition of NaCl) or ionic strength ≥ 20 mM NaCl (pH 7.0), with a predominant elastic gel-like behaviour observed at ≥ 20 mM NaCl. Resistance of MCNC-based Pickering emulsions to coalescence and responsiveness to flocculation at bio-relevant pHs and ionic strengths show promise in the design of delivery vehicles. Graphical abstract: Image 1 Highlights: Wettability of cellulose nanocrystals was altered using octenyl succinic anhydride. Pickering emulsions were stabilised by modified cellulose nanocrystals (MCNCs). Emulsions were resilient to coalescence when subjected to environmental stresses. Decreasing the pH to ≤ pH 4.0 led to aggregation of MCNC-stabilised droplets. Aggregated droplets demonstrated gel-like behaviour at ≥ 20 mM NaCl.